Beryllium doped graphene as an efficient anode material for lithium-ion batteries with significantly huge capacity: A DFT study. (December 2017) - Ullah, Saif; Denis, Pablo A.; Sato, Fernando
Graphical abstract: Be doped graphene is proposed for using as anode material in LIBs. The enhanced Li adsorption and huge storage capacity show that Be-graphene can be a best alternative to B-graphene. Highlights: Be doped graphene is proposed as anode material for LIBs and found much more efficient than B doped graphene. Be doping in a divacancy graphene can enhance the storage capacity. A maximum possible theoretical Li storage capacity of 2303.295 mAh/g is calculated for Li8 BeC7 . The Lithiation potential shows that Be doped graphene is the best choice for LIBs. Abstract: First-principles density functional theory (DFT) calculations were performed to investigate the lithium (Li) adsorption upon beryllium (Be) doped graphene. Be acts as hole doping in graphene leaving the structure as electron deficient, offering a greater tendency for Li adsorption than in pristine and boron (B) doped graphene. The introduction of Be augments the adsorption energy of Li from −1.11 to −2.53 eV/Li. Furthermore, 12, and 16 Li ions can easily be captured by one Be center in the single and double vacancy case, respectively, with the adsorption energies of −1.33 eV/Li (for both the cases), showing that Be doped graphene is an excellent anode material for lithium ion batteries (LIBs). Consequently, the presence of structural defects, in particular, a divacancy is found to be more efficient in terms of Li storage capacity. A huge Li storage capacity (2303.295 mAh/g) is calculated for Li8 BeC7 having reasonable adsorption energy (−1.47 eV/Li). Our calculated capacity is 6.19 times greater than that of the graphite.